2000
DOI: 10.2134/agronj2000.921144x
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crops for Sweet Corn Production in a Short‐Season Environment

Abstract: Legume cover crops can supply all or most of the N required by a subsequent crop if legume biomass is of sufficient quantity and N mineralization is approximately synchronous with crop demand. Three 2‐yr crop rotation cycles were conducted on a Lamoine silt loam (fine, illitic, nonacid, frigid Aeric Epiaquept) soil in Maine to (i) evaluate biomass and N accumulation of alfalfa (Medicago sativa L.), winter rye (Secale cereale L.), and hairy vetch (Vicia villosa Roth subsp. villosa) plus winter rye cover crops; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 24 publications
8
42
1
2
Order By: Relevance
“…Adequate summer rainfall (Table 3) Higher plant available N during the sweet corn season at Ridgetown than Bothwell (Table 7) provides some explanation as to why cover crops affected sweet corn yield in the 0 kg N ha (1 but not the 140 kg N ha (1 treatment at Bothwell and why there was no cover crop effect with or without N fertilizer at Ridgetown. In general, the positive effect of N fertilizer on total and marketable yield at Bothwell, and in total yield at Ridgetown was consistent with other research (Burket et al 1997;Mullins et al 1999;Griffin et al 2000;Cline and Silvernail 2002;Teasdale et al 2008). Similar to our study, Mullins et al (1999), Burket et al (1997), and Griffin et al (2000) observed variable weather during their studies, including hot dry years.…”
Section: Yield and Profit Marginssupporting
confidence: 92%
See 2 more Smart Citations
“…Adequate summer rainfall (Table 3) Higher plant available N during the sweet corn season at Ridgetown than Bothwell (Table 7) provides some explanation as to why cover crops affected sweet corn yield in the 0 kg N ha (1 but not the 140 kg N ha (1 treatment at Bothwell and why there was no cover crop effect with or without N fertilizer at Ridgetown. In general, the positive effect of N fertilizer on total and marketable yield at Bothwell, and in total yield at Ridgetown was consistent with other research (Burket et al 1997;Mullins et al 1999;Griffin et al 2000;Cline and Silvernail 2002;Teasdale et al 2008). Similar to our study, Mullins et al (1999), Burket et al (1997), and Griffin et al (2000) observed variable weather during their studies, including hot dry years.…”
Section: Yield and Profit Marginssupporting
confidence: 92%
“…In general, the positive effect of N fertilizer on total and marketable yield at Bothwell, and in total yield at Ridgetown was consistent with other research (Burket et al 1997;Mullins et al 1999;Griffin et al 2000;Cline and Silvernail 2002;Teasdale et al 2008). Similar to our study, Mullins et al (1999), Burket et al (1997), and Griffin et al (2000) observed variable weather during their studies, including hot dry years. As well, with the exception of the study by Teasdale et al (2008), which was conducted on loamy sand soil, the other studies (Burket et al 1997;Mullins et al 1999;Griffin et al 2000;Cline and Silvernail 2002) occurred predominately on silt loam soils and therefore were less sandy than the soils in our study.…”
Section: Yield and Profit Marginssupporting
confidence: 92%
See 1 more Smart Citation
“…In 2006/07 season, the differences between the mean protein content of green pods obtained from Pan 311 and Red Caloona was significant. The higher values obtained in Pan 311 was probably because of its early maturity status and better nutrients uptake ability including nitrogen (Griffin et al, 2000). Neither cropping systems nor cowpea leaf pruning during the vegetative stage had significant effect on the protein content of cowpea green pods.…”
Section: Protein Content Of Cowpea Green Pods As Affected By Differenmentioning
confidence: 90%
“…Other studies in both the USA and Ghana have shown that nitrogen yields from legumes planted the season before were between 100-200 kg/ha (Griffin et al 2000). In the organic systems at Rodale Farms in Pennsylvania, soil nitrogen levels were 43% compared to only 17% in conventional systems .…”
Section: Conserving Essential Nutrientsmentioning
confidence: 93%